Delirium following mechanical thrombectomy for ischemic stroke – individuals at risk, imaging biomarkers and prognosis - Hahn, Marianne; Brockstedt, Lavinia; Gröschel, Sonja; Geschke, Katharina; Grauhan, Nils F.; Brockmann, Marc A.; Othman, Ahmed E.; Gröschel, Klaus; Uphaus, Timo (Frontiers in Aging Neuroscience, 2025)
AimPost-stroke-delirium has been linked to worse outcome in patients with acute cerebrovascular disease; identification of individuals at risk may prevent delirium and thereby improve outcome. We investigate prognosis and factors associated with post-stroke-delirium in patients with large vessel occlusion (LVO) ischemic stroke treated by mechanical thrombectomy (MT).Methods747 patients (53.4% female) prospectively enrolled in the Gutenberg-Stroke-Study from May 2018–November 2022 were analyzed with regard to diagnosis of delirium. Group comparison of patient-, stroke- and treatment characteristics as well as computed tomography(CT)-imaging based parameters of cerebral atrophy (global cortical atrophy [GCA], posterior atrophy [Koedam], medial temporal lobe atrophy [MTA] scores) and white matter lesions (Fazekas score) was conducted. Independent predictors of delirium and the association of delirium with functional outcome at 90-day follow-up was investigated by multiple logistic regression analyses.ResultsWe report 8.2% of patients (61/747) developing delirium following MT of LVO. Independent predictors were older age (aOR[95%CI] per year: 1.034[1.005–1.065], p = 0.023), male sex (aOR[95%CI]: 2.173[1.182–3.994], p = 0.012), general anesthesia during MT (aOR[95%CI]: 2.455[1.385–4.352], p = 0.002), infectious complications (aOR[95%CI]: 1.845[1.031–3.305], p = 0.039), “other determined” etiology of stroke (aOR[95%CI]: 2.424[1.100–5.345], p = 0.028), and a MTA score exceeding age-specific cut-offs (aOR[95%CI]: 2.126[1.065–4.244], p = 0.033). Delirium was independently associated with worse functional outcome (aOR[95%CI]: 2.902[1.005–8.383], p = 0.049) at 90-day follow-up.ConclusionDelirium is independently associated with worse functional outcome after MT of LVO, stressing the importance of screening and preventive measures. Besides conventional risk factors, pathological MTA scores and use of general anesthesia during MT may be easy-to-apply criteria to identify individuals at risk of delirium and implement prevention strategies.